LEARNING ABOUT THE KNOWLEDGE OF WRITING POETRY USING METAPHORICAL THINKING APPROACH - Nina Nurhasanah; Wikanengsih Wikanengsih (JLER (Journal of Language Education Research), 2019)
Poetry is one of the materials in Indonesian-language-curriculum subject especially in Junior High School level. However, based on the field studies result, students still have difficulties to understand about poetry concepts. Therefore, researchers have submitted a solution for students to understand that concept of poetry can be easier by applying ‘Metaphorical Thinking’ approach that learns about the knowledge of poetry. The purpose of this research is to find out if Metaphorical Thinking approach is better in helping student to understand concept of poetry more than student who learns using conventional approach. The research method used is quasi experiment which means Nonequivalent Control Group Design. Furthermore, the samples in this research is 20 students of eight-grade from Innovative Al-Ibda Junior High School. Moreover, the technic of data analysis for students test result is by using SPSS 23. Based on the results in SPSS 23, it turned out that experiments class using Metaphorical Thinking approach gained better study result than control class. That result was proved by value Sig 0,000<0,05 in Independent Samples Test table. That result is also accorded with obtaining post-test average value in experiment class which is 80,5 while the average of control class is 64.